Health of Non-binary and Genderqueer People: A Systematic Review - Scandurra, Cristiano; Mezza, Fabrizio; Maldonato, Nelson Mauro; Bottone, Mario; Bochicchio, Vincenzo; Valerio, Paolo; Vitelli, Roberto (Frontiers in Psychology, 2019)
Background: Non-binary and genderqueer (NBGQ) people are those who do not identify within the gender binary system (male Vs. female), not falling exclusively in man/male or woman/female normative categories. A higher proportion of NBGQ people is usually found within young persons. This population is marginalized and, as such, is at risk of stigmatization and of developing negative health outcomes. As literature on the health of NBGQ people is sparse, this study aims at systematically review the limited studies on this field. Methods: The research questions which guided the systematic review were: (1) What are the differences in the health levels between NBGQ and binary transgender (BT) individuals? (2) What are the differences in the health levels between NBGQ and cisgender individuals? (3) Which medical and psychological interventions are most suitable for improving NBGQ health? According to PRISMA guidelines, a systematic search was conducted in PubMed, PsycInfo, Web of Science, and Google Scholar. Results: Eleven studies met the inclusion criteria for the current systematic review. Among them, 9 were focused on the health differences between NBGQ and BT individuals, 4 of the latter and 1 individually were focused on the health differences between NBGQ and cisgender individuals, and 1 was focused on the evaluation of health outcomes related to medical procedures. No studies assessed psychological interventions aimed at improving health in NBGQ individuals. All studies were cross-sectional, did not generally recruit a large sample of NBGQ individuals, and used non-probability sample design. Results related to the difference in health between NBGQ and BT were mixed; indeed, some found a better health status while others a worse one. Results related to the differences in health between NBGQ and cisgender highlighted higher health needs in NBGQ than in BT individuals. The only study analyzing the effects of medical interventions on health found that NBGQ female-assigned at birth individuals improved their quality of life after chest surgery. Conclusions: Although scholars are starting to pay attention to the NBGQ health, research needs to be expanded both in terms of methodology and research contents. Clinical, health-related social policies, and research recommendations in this field are reported.